Accessory Tibionavicular Muscle: An Unusual Cause of Medial Ankle Pain - Iyengar, Karthikeyan P.; Sharma, Gaurav Kant; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2023)
Accessory or anomalous muscles around the ankle are not uncommon and are usually asymptomatic. They are traditionally encountered during imaging undertaken for evaluation of ankle pain. We reported the first case of a new accessory muscle in the anteromedial part of the ankle with associated partial thickness tear in an 18-year-old football player presenting as symptomatic pathology. In this article, we described the role of cross-sectional imaging in its diagnosis including successful management of the condition with ultrasound-guided platelet-rich plasma therapy and review-associated literature.
Keywords: ankle; accessory muscles; ultrasound; magnetic resonance imaging; platelet-rich plasma; dry needling